In the search for the infinite servers queue with Poisson arrivals busy period distribution exponential behaviour - Ferreira, M. A. M. (2017)
This paper purpose is to investigate exponential behavior conditions for the M'G'oo; queue busy period length distribution. It is presented a general theoretical result that is the basis of this work. The complementary analysis rely on the M'G'oo; queue busy period length distribution moments computation. In M'G'oo; queue practical applications - in economic, management and business areas - the management of the effective number of servers is essential since the physical presence of infinite servers is not viable and so it is necessary to create that condition through an adequate management of the number of servers during the busy period.